The Analysis of Technology Acceptance SIDESA Application Using the Technology Acceptance Model 2 Method - Sihombing, Denny Jean Cross (STIKOM Tunas Bangsa Pematangsiantar, 2023)
SIDESA is a village information system that aims to assist village governments in managing information and data related to various aspects of village life. The goal is to improve administrative efficiency, community services, and decision-making at the village level. On the other hand, the digital divide in society affects the acceptance of technology in rural communities. Application technology acceptance analysis is necessary to understand how users and related parties will accept technology applications. This is done to identify technology applications' potential success or failure before they are widely launched. This research uses the TAM 2 technology acceptance model; data collection is done by distributing questionnaires online via google forms to the system user community. The data obtained were 133 respondents, and data processing was carried out using SmartPLS tools. The results showed a significant influence between Subjective Norm on Image, Output Quality on Perceived Usefulness, Perceived Ease of Use on Perceived Usefulness, Perceived Usefulness on Intention to Use, Perceived Ease of Use on Intention to Use, Intention to Use on Usage Behavior, and Experience on Intention to Use so that the acceptance of the SIDESA application has an effect based on the factors of usefulness (Perceived Usefulness), ease (Perceived Ease of Use), experience (Experience), Interest (Intention to Use), and the accuracy of the information presented (Output Quality).